Ženská mystika v kamaldulských reformních kázáních první poloviny 15. století - Stejskal, Jan (Univerzita Pardubice, 2003)
Its actors considered the first half of the 15th century as a period of the Church crisis. It is also period of several Church councils organized in order to resolve various problems of papacy., Czech Hussite heresy, the union of both Churches etc. Czech camaldolian hermit and participant of Siena council John Jerome of Prague (c. 1370-1440) started the way out from crisis within his own monastic order. His reform was focused on mystical experience of the popular and saint women Angela of Foligno and Catharine of Siena. In his camaldolian hermitage he prepared several sermons dealing with examples pf both women. Their experiences were used as the possible way of reform proposed by John Jerome to camaldolian community. The general reform has failed, let us reform individually, he preached and prepared the practical guide of monk to perfection. John Jerome used his experiences from the daily life of the community and also the "secret life" of its members - he surely knew as the official visitator of the order.
Keywords: náboženské poměry; reformy; 15. století; světci; mystika; Jan Jeroným z Prahy